Botulinum toxin in the management of facial paralysis. Issue 4 (August 2015) - Cabin, Jonathan A.; Massry, Guy G.; Azizzadeh, Babak
<x xml:space="preserve">Abstract</x> Purpose of review Complete flaccid facial paralysis, as well as the synkinetic and hyperkinetic sequelae of partial recovery, has significant impact on quality of life. Patients suffer from functional deficiencies, cosmetic deformity, discomfort and social consequences leading to emotional distress. Despite an extensive and sophisticated array of available interventions for facial reanimation, most patients have persistent issues that require consistent follow-up. In long-term management, botulinum toxin (BT) injection remains a critical tool in the treatment of the facial paralysis patient, particularly in the case of synkinesis, hyperkinesis and imbalance. We review the recent scientific literature and highlight key principles and developments in the use of BT in the management of facial paralysis, including less common applications for acute facial paralysis, hyperlacrimation and pseudoptosis. Recent findings We reviewed the literature for the latest advances in the use of BT in facial paralysis, including applications and technique, as well as measurement tools and adjunct exercises. We also share our experience in treating our own patient population. Summary BT continues to be a well tolerated and effective tool in the long-term management of facial paralysis, specifically in treating synkinesis, imbalance and hyperkinesis, as well as hyperlacrimation and pseudoptosis. Consistent measurement tools and adjunct neuromuscular retraining are crucial in the successful deployment of BT. Controversy exists as to whether BT should be used to manage facial paralysis during the acute phase, and whether BT application to the nonparalyzed face can improve long-term recovery in the paralyzed side.